Cellular Structures as Structured Simplicial Structures - Damiand, Guillaume; Lienhardt, Pascal (Combinatorial Maps, 2015)
So far we have been concerned with the definitions of n-Gmaps and n-maps, construction operations and embedding definitions for applications in geometric modeling, computational geometry, discrete geometry, computer graphics, image processing and analysis. But note that only examples of geometric objects which can be associated with n-Gmaps and n-maps have been provided. An important question remains: what are the geometric objects which correspond to n-Gmaps and n-maps, and more generally to cellular structures, including incidence graphs?